Sistem Pelaporan Keuangan Zakat Berbasis Teknologi Informasi Dan Transparasi Di BAZNAS Gresik - Warti'ah, Warti'ah; Arif, Choirul; Wirdah, Jazilatul (Program Studi Perbankan Syariah Institut Al-Fithrah (IAF) Surabaya, 2024)
The purpose of this study was to determine how the zakat financial reporting system is based on information technology and transparency at BAZNAS Gresik. The data analysis used is descriptive qualitative. The results of the study indicate that BAZNAS Gresik Regency has been transparent in zakat financial reporting which can be seen on the BAZNAS website and is updated every month. BAZNAS Gresik Regency continues to strive to always improve the quality of financial reports transparently in order to maintain public trust and continues to strive to make improvements to the information system so that its services can be more optimal.